Comparison of Outcome in Salbutamol Delivery through Metered Dose Inhaler versus Nebulizer in Children with Severe Acute Exacerbation of Asthma - Qadeer, Naima; Wamiq, Saba; Javeed, Asif; Javaid, Mian Adnan Aslam (Biological and Clinical Sciences Research Journal, 2025)
Asthma is one of the most common chronic respiratory diseases among children worldwide, and severe acute exacerbations remain a leading cause of morbidity and healthcare utilization. Salbutamol, a short-acting β2-agonist, is the mainstay of therapy, commonly delivered either by nebulizer or metered-dose inhaler (MDI) with a spacer. The optimal delivery method for children, particularly in resource-limited settings like Pakistan, remains debated. Objective: To compare the efficacy of salbutamol delivered via nebulizer versus MDI with a spacer in children presenting with severe acute asthma exacerbations. Methods: This randomized controlled trial was conducted at the Department of Pediatric Medicine, Ibn-e-Siena Hospital, Multan, over a six-month period from May 2024 to October 2024. A total of 104 children aged 5–15 years with severe acute exacerbation of asthma (Pulmonary Score ≥7) were randomized into two groups: nebulizer (n=52) and MDI with spacer (n=52). Baseline demographic and clinical characteristics were recorded. All participants received adjunctive intravenous methylprednisolone and magnesium sulfate. The primary outcome was a reduction in respiratory rate at 20 minutes. Secondary outcomes included the change in pulmonary score at 4 hours and the requirement for hospitalization. Data were analyzed using SPSS version 23, with p < 0.05 considered significant. Results: The mean age of participants was 9.8 ± 2.7 years; 60.6% were male. At 20 minutes, the MDI group demonstrated a significantly greater reduction in respiratory rate compared to the nebulizer group (8.6 ± 2.4 vs. 6.9 ± 2.7 breaths/min, p = 0.002). At 4 hours, the MDI group had a lower mean pulmonary score (3.1 ± 1.2 vs. 3.8 ± 1.4, p = 0.01). Hospitalization was required in 7.7% of children in the MDI group, compared to 17.3% in the nebulizer group, although this difference was not statistically significant (p = 0.14). Stratified analyses confirmed consistent superiority of MDI across most subgroups. Conclusion: MDI with a spacer proved more effective than a nebulizer in improving short-term respiratory outcomes in children with severe acute asthma exacerbations. Given its comparable efficacy, ease of use, and reduced need for specialized equipment, MDI with a spacer represents a practical and effective alternative to nebulization in resource-constrained pediatric emergency settings.